Comparing Rest Alone to Bandaging and Rest in Horses With Superficial Digital Flexor Tendinopathy - Alzola, Rafael; Freeman, Sarah Louise (Veterinary Evidence, 2019)
PICO question In horses with superficial digital flexor tendonitis is bandaging and rest compared to rest alone more effective at promoting healing? Clinical bottom line There is currently a lack of scientific evidence to suggest that bandaging promotes effective tendon healing following injury. However, rigid bandages significantly limit lesion propagation in equine superficial digital flexor (SDF) tendinopathies. The result of this PICO question suggests that a short period (ten days) of cast immobilisation during the initial inflammatory phase of the injury improves prognosis by limiting lesion propagation. The level of confidence in the outcomes from the body of evidence in the four studies identified is moderate.